Design considerations of small-animal SPECT cameras - Meikle, S.; Kench, P.; Lin, Jianyu (Springer New York, 2014)
Single photon emission computed tomography (SPECT) is a tomographic imaging modality based on the radiotracer principle [1]. It is used to measure the 3D distribution of radiolabelled molecules in vivo using very sensitive radiation detectors and mathematical image reconstruction algorithms. Although SPECT has been used as a clinical tool for several decades, it is also well suited to imaging small animal models of human disease, such as laboratory mice and rats, for pre-clinical research. Because of the relatively long physical half-lives of single photon emitters (Table 4.1), SPECT is best suited to the study of macromolecules, such as antibodies and proteins, which have relatively slow rates of accrual at their target sites and slow plasma clearance. Additionally, proteins and antibodies are easily labelled with one of the radioisotopes of iodine (125I, 123I or 131I), or else by attaching a chelating agent incorporating one of the other common single photon emitters with suitable imaging properties, such as 99mTc or 111In. Conversely, the closely related radiotracer technique positron emission tomography (PET), which is discussed in the following chapter, is best suited to the study of small molecules such as synthetic drugs which have relatively fast kinetics in the body. Thus, the two techniques are highly complementary in the pre-clinical research environment.